Revisiting allonomes of Latvian personal names of the 17th century - Siliņa-Piņķe, Renāte (Baltistica, 2023)
The article analyses a topical and infrequent theoretical issue in the historical study of personal names in Latvian onomastics, and the possibilities of practical application. The article aims at actualising the term allonome in Latvian historical onomastics and approbating its usage by synchronously evaluating Latvian personal names in the sources of the first half of the 17th century. 67 groups of allonomes were identified altogether, the biggest of which include even more than 15 allonomes. The allonomic chains diverse in spelling are characteristic of inconsistent Early New High German spelling, and they exhibit a clash of the information submitted by Latvian peasants with the established range of German personal names known by the authors of the texts, which creates a German-Latvian mixture with the dominant German language. All the data lead to conclusions about the connection of diverse spelling forms of Latvian personal names to the sources in the Early New High German. They help either unify or divide forms of personal names thus inducing a further cultural and historical analysis of Latvian personal names in the 17th century. Allonomes identified in the framework of a single source, preferably several times, have a higher degree of plausibility. However, particularly unique cases of allonomes in the sources should be evaluated with caution. Valuable findings include the connection of Latvianised forms to the corresponding German personal names, for example, Laurentz = Lauring, Gert = Jerkis, Clauß = Clawing or Arendt = Arinß, etc. The analysis results in a conclusion that the influence of the spelling of the 17th century German in the records of personal names should be analysed before identifying allonomes; namely, spelling variants should be collected and interpreted as allographs of a single name. Such an approach would permit the reduction of the number of allonomes and help focus on crucial differences. The conclusions also highlight problematic cases in the analysis and provide tentative suggestions for further future research.